2006
DOI: 10.1186/1745-6673-1-20
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of skeletal muscle fatigue of road maintenance workers based on heart rate monitoring and myotonometry

Abstract: ObjectiveThis research work is dedicated to occupational health problems caused by ergonomic risks. The research object was road building industry, where workers have to work very intensively, have long work hours, are working in forced/constrained work postures and overstrain during the work specific parts of their bodies. The aim of this study was to evaluate the work heaviness degree and to estimate the muscle fatigue of workers after one week work cycle. The study group consisted of 10 road construction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Assessment of the functional state of skeletal muscles and muscle fatigue was carried out using myotonometric measurements performed with MYOTON-3 device created in Estonia, the University of Tartu. Theoretical concept of MYO is described in references [ 23 , 24 ], as well as in our earlier publication describing results of the research on skeletal muscle fatigue of road maintenance workers[ 25 ]. The working principle of MYO lies in using acceleration probe to record how peripheral skeletal muscle or its part reaction to the mechanical impact (testing end mass 20 grams, duration 15 milliseconds) and the following analysis of the resulting signal.…”
Section: Methodsmentioning
confidence: 99%
“…Assessment of the functional state of skeletal muscles and muscle fatigue was carried out using myotonometric measurements performed with MYOTON-3 device created in Estonia, the University of Tartu. Theoretical concept of MYO is described in references [ 23 , 24 ], as well as in our earlier publication describing results of the research on skeletal muscle fatigue of road maintenance workers[ 25 ]. The working principle of MYO lies in using acceleration probe to record how peripheral skeletal muscle or its part reaction to the mechanical impact (testing end mass 20 grams, duration 15 milliseconds) and the following analysis of the resulting signal.…”
Section: Methodsmentioning
confidence: 99%
“…The values of stiffness are in the range of 150 N/m to 300 N/m, depending on the type of the muscle. The results of "myotonometric" measurement of workers in different occupations can be found in [6][7][8]. The aim of the study is to determine the fatigue of muscles during the work process in the garment industry.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in muscle tone indicates an abnormal state in the musculoskeletal system and it is used as an indicator of muscle fatigue 20 ) . Roja et al reported that with additional lifting and lowering of heavy goods, muscle tone of workers increased further, whereas workers without such repetitive work showed relatively less muscle tone 21 ) . In addition, muscle tone was shown to correlate with EMG frequency and a decrease in muscle fatigue increases muscle tone as well 22 ) .…”
Section: Discussionmentioning
confidence: 99%